Youth Labor in Transition 2018
DOI: 10.1093/oso/9780190864798.003.0016
|View full text |Cite
|
Sign up to set email alerts
|

What are the employment prospects for young Estonian and Slovak return migrants?

Abstract: This chapter addresses patterns of return migration in Estonia and Slovakia. It investigates the selection of emigrants who decide to return home and analyzes their characteristics compared to emigrants who remain abroad and to fellow nationals who did not emigrate, as well as the labor market status of young returnees after re-entering the domestic labor market. The comparative analysis of the two national Labor Force Survey samples suggests that among young returnees, level of education has no association wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Dumont and Spielvogel (2008) argue that the different macroeconomic context in the home country and in the host country is a major determinant of the decision to return. This assumption motivated researchers to study an association between return migration patterns in response to the 2008/2009 economic crisis (Kahanec -Zimmermann 2016;Galgóczi et al 2012;Masso et al 2018).…”
Section: Reasons For Return Migrationmentioning
confidence: 99%
See 4 more Smart Citations
“…Dumont and Spielvogel (2008) argue that the different macroeconomic context in the home country and in the host country is a major determinant of the decision to return. This assumption motivated researchers to study an association between return migration patterns in response to the 2008/2009 economic crisis (Kahanec -Zimmermann 2016;Galgóczi et al 2012;Masso et al 2018).…”
Section: Reasons For Return Migrationmentioning
confidence: 99%
“…Research focusing on the CEE region has also looked specifically at the influence of over-education in host countries' labour markets on return decisions or reintegration patterns. On an individual level, a mismatch between skills and jobs abroad, which has been severe for CEE migrants in the West (Voitchovsky 2014), has been identified as a key determinant of the return of Estonian migrants working in Finland (Pungas et al 2012), but also more generally (Masso et al 2018). Similarly, Currie (2007) found that Polish returnees commonly frame their decision to return to Poland within the context of frustration with limited labour market progress in the UK.…”
Section: Reasons For Return Migrationmentioning
confidence: 99%
See 3 more Smart Citations